Fracture characterization of fractured rock bodies based on acoustic and optical characteristics - Zhang, Jiyong; Zou, Qianjin; Guan, Huadong (Frontiers in Earth Science, 2024)
Crack propagation is an important cause of damage to rock bodies. In this study, uniaxial compression tests were conducted on specimens with rock-like mass containing fissures with different inclination angles to study the effect of crack angle on the crack evolution and fracture characteristics of rock bodies. The specimen surface deformation and internal response characteristics during fracture were analyzed via digital image correlation (DIC) and acoustic emission (AE) techniques. The results indicated that the AE characteristics of the fractured specimens exhibited a high degree of activity during the pore compaction and crack propagation stages. The prefabricated fissure configuration affected the stress state at the fissure tip, leading to differences in the crack evolution paths and rupture modes of fissure specimens with different angles. Under the uniaxial peak intensity, the relative position of the normalized global strain curve peak point gradually shifted from the specimen tip to the middle of the specimen as the crack angle increased, which corresponded to the shear damage-tension-shear mixed damage-tension damage modes of the specimen. The findings of this study indicate that normalized global strain curves can reflect the characteristics of crack evolution and provide a basis for the discrimination of fissured rock mass damage modes.